Dampak Desentralisasi Fiskal di Indonesia terhadap Pertumbuhan Ekonomi dan Disparitas Antar Daerah: Analisa Model Makro Ekonometrik Simultan - Dartanto, Teguh; Brodjonegoro, Bambang P. S. (UI Scholars Hub, 2003)
From January 1, 2001, when new autonomy laws were implemented. Indonesia began to move toward decentralization of what had been a highly decentralized. This policy adopts two complimentary laws. Law No. 22/1999, which basically the devolution policy, has been accompanied by Law No. 25/1999, which basically reflect that decentralization policy in Indonesia has adopted the concept of